2008
DOI: 10.1002/anie.200701980
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Assemblies Based on Organometallic Quinonoid Linkers: A New Class of Coordination Networks

Abstract: Self-assembly of coordination frameworks exhibiting original architectures is an active area of research. Generally, such assemblies are constructed from organic spacers and transition metals of different geometrical structures. Herein, we report a novel class of supramolecular coordination assemblies with organometallic linkers based on metalated quinonoid and thioquinonoid complexes that serve as spacers. The organometallic ligands are stable and have the general formula [Cp*M(eta(4)-benzoquinone)] (o- and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 72 publications
0
41
0
Order By: Relevance
“…In efforts to expand our understanding of hydrogen bonding in binfunctional systems, we are looking at other metal fragments. The rich and unusual chemistry enabled by the Cp*Ir fragment [56][57][58][59][60][61] led us to explore it as a platform. In particular, chloro and hydride complexes of Cp*Ir monophosphine fragments have been versatile starting materials or intermediates.…”
Section: Model Studies On Other Metal Fragmentsmentioning
confidence: 99%
“…In efforts to expand our understanding of hydrogen bonding in binfunctional systems, we are looking at other metal fragments. The rich and unusual chemistry enabled by the Cp*Ir fragment [56][57][58][59][60][61] led us to explore it as a platform. In particular, chloro and hydride complexes of Cp*Ir monophosphine fragments have been versatile starting materials or intermediates.…”
Section: Model Studies On Other Metal Fragmentsmentioning
confidence: 99%
“…[11][12][13][14] Some of these complexes exhibited useful luminescent properties. 15,16 Unlike the p-benzoquinone metal complexes the related obenzoquinone compounds can be used as OM-chelates to generate new chiral assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…Four novel Cu I -Ph 2 bpm/C 2 H 4 adducts that turned out to be three-dimensionally self-assembled by an intermolecular π-π stacking interaction and a C-H···N contact were isolated and characterized by X-ray, 1 H NMR, IR and TG-DTA analyses. There is growing interest in the relevance of weak supramolecular interactions, such as C-H···O and C-H···N hydrogen bonds [33][34][35][36] and π-π interactions, [37][38][39][40] for molecular packing and coordination in the context of supramolecular crystal engineering. It was found that these weak interactions can drive the crystallization process and select a particular molecular structure.…”
Section: Introductionmentioning
confidence: 99%